AB0163 No Association between The Percentage of Memory or Transitional B Regs and Disease-Related Autoantibodies in Systemic Sclerosis. (15th July 2016) - Mavropoulos, A.; Liaskos, C.; Simopoulou, T.; Varna, A.; Katsiari, C.G.; Bogdanos, D.P.; Sakkas, L.I.
Abstract : Background: Recently, we found that Breg cells are numerically decreased and functionally impaired in patients with systemic sclerosis (SSc) 1 A subsequent study confirmed these data and reported a negative correlation between Breg levels and the titres of anti-topo I and anti-centromere antibodies (ab) in patients with SSc 2 . Objectives: To assess the relation between memory or transitional Bregs with SSc-specific anti-topo I, anti-centromere (CEN) and anti-RNA pol I abs in our cohort of SSc patients. Methods: Fifty patients with Ssc were tested for disease-specific abs (Topo I, CENP, RNA pol I) using line blot analysis (EUROIMMUN), and for memory [CD19(pos)CD27(pos)CD24(high)] and transitional [CD19(pos)CD24(high)CD38(high)] Bregs using flow cytometry. Results: Anti-CEN, anti-Scl-70 and RNA pol I abs were present in 12 (24%), 23 (46%) and 7 (14%) patients with SSc, respectively. The % of memory and transitional B regs was comparable between anti-CEN ab-positive and -negative patients (1.56±1.40 vs 1.74±1.01 and 0.78 ±0.73 vs 0.65±0.68 respectively, p>0.05), and also beween anti-RNA ab-positive and -negative patients with SSc (1.96±1.26 vs 1.65±1.09 and 0.54±0.53 vs 0.7±0.72 respectively). While the % of memory Bregs did not differ between anti-topo I-positive and -negative patients (1.96±1.26 vs 1.65±1.09 and 0.54 ±0.53 vs 0.7±0.72 respectively), the % of transitional Bregs tended to be decreased in patients with anti-topo I-positive compared to anti-topo I ab-negative patients (0.49±0.46 vs 0.84±0.61 p=0.066). Levels of B regs (memory or transitional) did not negatively correlate with autoantibody titres by line blot analysis. Conclusions: We failed to find an association between percentages of memory and transitional B regs with SSc-specific autoantibodies. References: Mavropoulos A et al Arthritis Rheumatol 2016;68:494–504 Matsushita T et al Rheumatology 2016;55:263–7 Acknowledgement: Financial support by ELKE, University of Thessaly Disclosure of Interest: None declared